Pengaruh Pelatihan Dan Budaya Organisasi Terhadap Produktivitas Kerja Pegawai Pada Dinas Penanaman Modal & PTSP Kota Palopo - Febrianti Febrianti; Ardiansyah Ardiansyah; Nabila Nursaid; Wanda Wanda; Ishak Runi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the influence of training and organization culture to work productivity. Respondent study This is all non-ASN employees at Dinas Penanaman Modal dan PTSP Kota Palopo . Collection of this data carried out in May 2024. Data were obtained using a questionnaire that was distributed randomly and measured with a Likert scale unit. The data obtained were then analyzed using multiple regressionRespondent study This chosen with use method simple random sampling technique (slovin’s formula) , with amount sample as many as 43 non-ASN employees . Study This is study quantitative with using SPSS version 25. Findings study This show that Training and Culture Organization You're welcome influential to Productivity Work. This means that the better the training and organizational culture, the better the work productivity of employees at Dinas Penanaman Modal dan PTSP Kota Palopo, training has a positive and insignificant effect on work productivity at Dinas Penanaman Modal dan PTSP Kota Palopo, and organizational culture has a positive and significant influence. on Work Productivity.